2017
DOI: 10.5301/jbm.5000255
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Combination of CEA and Tumor Budding to Identify High-risk Patients with Stage II Colon Cancer

Abstract: The findings indicate that the combination of CEA levels and tumor budding grade has greater prognostic value for identifying patients with stage II colon cancer who are at high-risk for disease progression, than either marker alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…CEA is a glycoprotein involved in cell adhesion processes during the fetal development of gastrointestinal tissue 42 . Currently, increasing attention has been paid to CEA as a biomarker for diagnosis and predicting prognosis in ICC patients 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…CEA is a glycoprotein involved in cell adhesion processes during the fetal development of gastrointestinal tissue 42 . Currently, increasing attention has been paid to CEA as a biomarker for diagnosis and predicting prognosis in ICC patients 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been inferred that the efficacy of adjuvant chemotherapy is limited to patients with stage II CRC and with potentially high‐risk clinicopathological characteristics. In this context, various biomarkers of high malignancy have been proposed in many clinical studies . In particular, tumour budding has been repeatedly reported to contribute to the selection of patients with this type of stage II cancer …”
Section: Introductionmentioning
confidence: 99%
“…In this context, various biomarkers of high malignancy have been proposed in many clinical studies. [14][15][16][17][18][19] In particular, tumour budding has been repeatedly reported to contribute to the selection of patients with this type of stage II cancer. [4][5][6][7]20,21 The prospect of using artificial intelligence (AI) to evaluate cytokeratin-stained slides has emerged as a potential option for the future.…”
mentioning
confidence: 99%
“…For example, in Li et al's study, the AUCs for PFS and OS of ALB were 0.644 and 0.611, respectively, and ALB alone was not an independent prognostic factor when compared to PLR [11]; in both ALB and cholinesterase high groups would have a better DSS than others; however, the AUCs of the combined groups were not compared with individual ALB (0.71) and cholinesterase (0.69) in their study [22]. Some authors tried to combine CEA with Ki-67 [49], p53 [50], tumor budding [51], CD44v6 [52], peritoneal carcinomatosis index [53], D-dimer [54] and NLR [55] to generate new prognostic indicators, but these studies did not compare the AUC of the new indicators with individual CEA. In our study, we found that ACR displayed the largest AUC when compared with individual ALB, CEA and NLR, LMR, PLR both for PFS and OS, which supports its priority in prognosis prediction in CRC.…”
Section: Discussionmentioning
confidence: 97%
“…[22]. Some authors tried to combine CEA with Ki-67 [49], p53 [50], tumor budding [51], CD44v6 [52], peritoneal carcinomatosis index [53], D-dimer [54] and NLR [55] to generate new prognostic indicators, but these studies did not compare the AUC of the new indicators with individual CEA. In our study, we found that ACR displayed the largest AUC when compared with individual ALB, CEA and NLR, LMR, PLR both for PFS and OS, which supports its priority in prognosis prediction in CRC.…”
Section: Discussionmentioning
confidence: 99%